Credit and Financial Access in Nepalese Agriculture: Prospects and Challenges - Pandey, A. (Journal of Agriculture and Environment, 2022)
The credit and financial access are urgent needs for agricultural development. This paper has attempted to find out present status of agricultural credit and their prevalent challenges and problems. The study is fully based on the statistical data, reports and findings of MoALD, MoF, NPC, NRB, and other relevant publications. The Government has targeted to expand agricultural credit through banking and financial institutions (BFIs) by implementing several acts, policies, strategies and programs through NRB, MoALD and MoF. However, constraints like credit ceiling, high value collateral demand, limited redemption facilities, limited agriculture insurance, financial illiteracy, lack of farmer friendly technologies, and poor monitoring and regulation of BFIs are responsible for lower credit expansion. Thus to promote and motivate BFIs and farmers to invest in agriculture, government need to address these challenges. The study also suggests to segregate farmer according to demand of credit volume and expand the branchless banking.